Preclinical evaluation of (111)In-DTPA-INCA-X anti-Ku70/Ku80 monoclonal antibody in prostate cancer - Evans-Axelsson, Susan (e-Century Publishing Corporation, 2014)
The aim of this investigation was to assess the Ku70/Ku80 complex as a potential target for antibody imaging of prostate cancer. We evaluated the in vivo and ex vivo tumor targeting and biodistribution of the (111)In-labeled human internalizing antibody, INCA-X ((111)In-DTPA-INCA-X antibody), in NMRI-nude mice bearing human PC-3, PC-3M-Lu2 or DU145 xenografts. DTPA-conjugated, non-labeled antibody was pre-administered at different time-points followed by a single intravenous injection of (111)In-DTPA-INCA-X. At 48, 72 and 96 h post-injection, tissues were harvested, and the antibody distribution was determined by measuring radioactivity. Preclinical SPECT/CT imaging of mice with and without the predose was performed at 48 hours post-injection of labeled DTPA-INCA-X. Biodistribution of the labeled antibody showed enriched activity in tumor, spleen and liver. Animals pre-administered with DTPA-INCA-X showed increased tumor uptake and blood content of (111)In-DTPA-INCA-X with reduced splenic and liver uptake. The in vitro and in vivo data presented show that the (111)In-labeled INCA-X antibody is internalized into prostate cancer cells and by pre-administering non-labeled DTPA-INCA-X, we were able to significantly reduce the off target binding and increase the (111)In-DTPA-INCA-X mAb uptake in PC-3, PC-3M-Lu2 and DU145 xenografts. The results are encouraging and identifying the Ku70/Ku80 antigen as a target is worth further investigation for functional imaging of prostate cancer.